Pathways of lignocellulosic biomass deconstruction for biofuel and value-added products production. (15th June 2022) - Ahmed, Shams Forruque; Mofijur, M.; Chowdhury, Sidratun Nur; Nahrin, Muntasha; Rafa, Nazifa; Chowdhury, Anika Tasnim; Nuzhat, Samiha; Ong, Hwai Chyuan
Highlights: Physical and chemical pretreatment show great effectiveness but need huge energy. Biological pretreatment can address most challenges but with long incubation times. Hybrid technologies gain popularity and improve the chemical yield. Pretreatment of lignocellulosic biomass account for 40% of total production costs. Optimization of process parameters need for techno-economically feasible. Abstract: As the world attempts to transition from fossil fuels, lignocellulosic biomass (LCB) serves as a promising alternative due to its high abundance. Hydrolysing LCB can generate various bioproducts, such as biofuels and value-added chemicals. However, the presence of lignin inhibits the solubilization of LCBs, presenting a major techno-economic challenge in the biorefinery concept. Therefore, this paper addresses the gaps left by most of the recent review works that fail to comprehensively review different pretreatment methods and the full scope of applications of LCBs, and do not incorporate techno-economic considerations of the technologies, the latter being the greatest bottleneck in the commercialization of the processes. The literature review revealed that while many of the physical and chemical pretreatment methods exhibit great effectiveness, they have a huge dependence on energy, chemicals, water, and/or specialized equipment, and produce harmful waste and inhibitory compounds. The pretreatment of lignocellulosic biomass can account for 40% of total production costs. Biological pretreatment can address these challenges but is limited by long incubation times. For instance, the bacterial pretreatment can noticeably reduce sawdust cellulose, hemicelluloses, and lignin contents by 35.8%, 37.1%, and 46.2%, respectively. Recently, integrated/coupling (hybrid) methods, such as chemical-assisted liquid hot water/steam and microwave or ultrasound-assisted alkaline pretreatment, have been gaining popularity due to their potential to improve chemical yield, but at the expense of the high cost of operation. To make pretreatment processes more techno-economically feasible, there is a need for process integration and the standardization and optimization of process parameters.